PENATAAN ULANG KEWENANGAN PENYIDIKAN DAN PENUNTUTAN DALAM PENEGAKAN HUKUM PELANGGARAN HAM BERAT - Ramadhan, Febriansyah; Nugraha, Xavier; Felany, Patricia Inge (Faculty of Law, Parahyangan Catholic University, 2020)
This article discusses the problems encountered in the preliminary court proceeding of gross human right violation cases in Indonesia. Identified are two state institutions, i.e. the National Human Right Commission and the Attorney General, who possess the authority to initiate investigation and subsequent successful prosecution of gross human right violation cases. Good cooperation and relation between these two agencies is therefore a must. This article looks into the problems encountered by these two institutions in doing the preliminary process and discusses possible redistribution of these two state agency authorities. To do this a doctrinal approach will be used.